Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro. Issue 12 (2nd July 2013) - Knaup, Karl Xaver; Monti, Juliana; Hackenbeck, Thomas; Jobst‐Schwan, Tilmann; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Juergen; Amann, Kerstin; Eckardt, Kai‐Uwe; Warnecke, Christina; Wiesener, Michael Sean
Abstract: Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF‐regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut‐1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF‐1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co‐localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, Inc.